Bisphenol A and bisphenol S both disrupt ovine granulosa cell steroidogenesis but through different molecular pathways - Ophélie Téteau; Anaïs Vitorino Carvalho; Pascal Papillier; Béatrice Mandon-Pépin; Luc Jouneau; Peggy Jarrier-Gaillard; Alice Desmarchais; Marie-Emilie Lebachelier de la Riviere; Claire Vignault; Virginie Maillard; Aurélien Binet; Svetlana Uzbekova; et al. (BMC, 2023)
Abstract Background Ovarian granulosa cells (GC) are essential for the development and maturation of a proper oocyte. GC are sensitive to endocrine disruptors, including bisphenol A (BPA) and its analogue bisphenol S (BPS), plasticisers present in everyday consumer products. BPA exhibits greater binding affinity for the membrane oestrogen receptor (GPER) than for the nuclear oestrogen receptors (ERα and ERβ). Here, we analysed the effects of BPA and BPS on the steroidogenesis of ovine GC in vitro, as well as their early mechanisms of action, the ovine being a relevant model to study human reproductive impairment. Disruption of GC steroidogenesis might alter oocyte quality and consequently fertility rate. In addition, we compared the effects of a specific GPER agonist (G-1) and antagonist (G-15) to those of BPA and BPS. Ewe GC were cultured with BPA or BPS (10 or 50 µM) or G-1 (1 µM) and/or G-15 (10 µM) for 48 h to study steroidogenesis. Results Both BPA and BPS (10 µM) altered the secretion of progesterone, however, only BPS (10 µM) affected oestradiol secretion. RNA-seq was performed on GC after 1 h of culture with BPA or BPS (50 µM) or G-1 (10 µM), followed by real-time PCR analyses of differentially expressed genes after 12, 24 and 48 h of culture. The absence of induced GPER target genes showed that BPA and BPS did not activate GPER in GC after 1 h of treatment. These molecules exhibited mainly independent early mechanisms of action. Gene ontology analysis showed that after 1 h of treatment, BPA mainly disrupted the expression of the genes involved in metabolism and transcription, while BPS had a smaller effect and impaired cellular communications. BPA had a transient effect on the expression of CHAC1 (NOTCH signalling and oxidative balance), JUN (linked to MAPK pathway), NR4A1 (oestradiol secretion inhibition), ARRDC4 (endocytose of GPCR) and KLF10 (cell growth, differentiation and apoptosis), while expression changes were maintained over time for the genes LSMEM1 (linked to MAPK pathway), TXNIP (oxidative stress) and LIF (cell cycle regulation) after 12 and 48 h, respectively. Conclusion In conclusion, although they exhibited similar effects, BPA and BPS impaired different molecular pathways in GC in vitro. New investigations will be necessary to follow the temporal changes of these genes over time, as well as the biological processes involved.